1991
DOI: 10.1126/science.1847755
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle-dependent Coupling of the Calcitonin Receptor to Different G Proteins

Abstract: Calcitonin is a calcium regulating peptide hormone with binding sites in kidney and bone as well as in the central nervous system. The mechanisms of signal transduction by calcitonin receptors were studied in a pig kidney cell line where the hormone was found to regulate sodium pumps. Calcitonin receptors activated the cyclic adenosine monophosphate (cAMP) or the protein kinase C (PKC) pathways. The two transduction pathways required guanosine triphosphate (GTP)-binding proteins (G proteins) (the choleratoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(53 citation statements)
references
References 47 publications
3
49
1
Order By: Relevance
“…8B). protein, and a subsequent switch from the adenylyl cyclase to the Ca 2ϩ /protein kinase C signal pathway was reported for the calcitonin receptor in a pig kidney cell line (35). For the parathyroid hormone receptor, an additional coupling to G i proteins and a subsequent increase in Ca 2ϩ influx depending on cell cycle was shown in osteogenic sarcoma cells (36).…”
Section: Resultsmentioning
confidence: 90%
“…8B). protein, and a subsequent switch from the adenylyl cyclase to the Ca 2ϩ /protein kinase C signal pathway was reported for the calcitonin receptor in a pig kidney cell line (35). For the parathyroid hormone receptor, an additional coupling to G i proteins and a subsequent increase in Ca 2ϩ influx depending on cell cycle was shown in osteogenic sarcoma cells (36).…”
Section: Resultsmentioning
confidence: 90%
“…The CTR, like other members of this family, is known to couple to multiple trimeric G proteins that activate several signaling molecules, thereby producing diverse biological responses in different cell types. For example, we and others have shown that some aspects of the osteoclast (OC) response to CT are mediated by the cAMP pathway, while others are mediated by protein kinase C (5,6), and studies in our laboratory, using synchronized LLC-PK1 kidney proximal tubule cells, have shown that the mode of receptor coupling and the biological effects of CT vary with the stage of the cell cycle (7,8). The coupling of a recombinant CTR to both the adenylyl cyclase and phospholipase C signaling pathways has been demonstrated (9,10).…”
mentioning
confidence: 99%
“…Manse-DPII is shorter (30 residues) than other known DH and has lower sequence similarity with other DH than does Manse-DH. However, in 1998, we identified a second DH from Tenebrio molitor, termed Tenmo-DH 47 (12) to distinguish this peptide from the known Tenmo-DH 37 (11). More recently we identified two DH from Hyles lineata (a sphingid moth closely related to M. sexta), Hylli-DH 30 and Hylli-DH 41 , which each differ at only one residue from their M. sexta counterparts.…”
mentioning
confidence: 99%
“…However, they are most likely paralogous sequences (arising from a gene duplication event), as is the case for fish CRF and urotensin I. The lower potency of Tenmo-DH 47 vs. Tenmo-DH 37 (12) suggests for it a somewhat different role, just as urocortin, an orthologue of urotensin I (15), has effects that differ in vivo from those of CRF (16,17).…”
mentioning
confidence: 99%